BS21 Stabilisation of suppressor of cytokine signalling 3 (SOCS3) to inhibit human saphenous vein smooth muscle cell proliferation and vascular stenosis. (4th June 2021) - Palmer, Tim; Moshapa, Florah; Willliams, Jamie; Riches-Suman, Kirsten; Elies, Jacobo
Abstract : Introduction: Suppressor of cytokine signalling 3 (SOCS3) limits multiple signalling pathways involved in vascular inflammation and remodelling responsible for neointimal hyperplasia and vein graft failure. However, SOCS3 function is limited by its short biological half-life, suggesting that SOCS3 stabilisation might prove an effective therapeutic strategy. Through identification of SOCS3 ubiquitination sites, we have engineered a novel SOCS3 transgene resistant to proteasomal degradation and assessed its ability to limit signalling pathways and processes responsible for neointimal hyperplasia. Methods: Flag-tagged SOCS3 transiently expressed in HEK293 cells was immunoprecipitated with anti-Flag antibody and fractionated by SDS-PAGE for trypsin digestion. Tryptic peptides were analysed by liquid chromatography and tandem mass spectrometry, and ubiquitination sites identified from di-Gly-modified SOCS3 peptides. Smooth muscle cells (SMCs) and endothelial cells (ECs) from human saphenous vein (HSV) were transduced with recombinant lentiviruses (LVs) with MOIs ranging from 3.6-22.2 tfu/cell. Ubiquitination was assessed by immunoprecipitation of soluble cell lysates and immunoblotting. Half-lives of SOCS3 transgenes were determined by immunoblotting following HSVSMC incubation ± protein synthesis inhibitor emetine. HSVSMC proliferation was assessed by cell counting. Finally, effects of WT and Lys-less SOCS3 gene delivery on cell signalling was determined by assessing phosphorylation of STAT3 (Tyr705) and ERK1/2 (Thr202/Tyr204) by immunoblotting. Results: Analysis of recombinant SOCS3 immunoprecipitated from HEK293 cells revealed that 8 of the 9 Lys residues in human SOCS3 were ubiquitinated. A mutated SOCS3 in which all 9 Lys residues were mutated to Arg was resistant to ubiquitination compared to wild type (WT) SOCS3. LV transduction of WT and Lys-less SOCS3 in HSVSMCs and ECs was highly efficient with >90% of cells expressing SOCS3 transgene after 48 hours. Lys-less SOCS3 was significantly more stable, displaying a biological half-life >4 hours versus <4 hours for WT (n=6, p<0.001). Despite these differences, WT and Lys-less SOCS3 were functionally equivalent in their ability to selectively inhibit STAT3 phosphorylation in response to either sIL-6Rα/IL-6 (74±6% and 80±7% inhibition respectively; n=4, p<0.05 versus controls) or PDGF-BB (67±17% and 72±18% inhibition respectively; n=5) but not ERK1/2 phosphorylation. However, while WT and Lys-less SOCS3 each inhibited cell proliferation in response to sIL-6Rα/IL-6 (83±29% and 89±22% inhibition respectively; n=4, p<0.05 versus controls) only Lys-less SOCS3 significantly inhibited PDGF-BB-stimulated proliferation (67±11% inhibition; n=4, p<0.05 versus controls). Conclusions: These results provide evidence for possible therapeutic targeting of SOCS3 stabilisation to limit HSVSMC dysfunction responsible for vein graft failure. Conflict of Interest: None